2022
DOI: 10.1016/j.ijchp.2021.100278
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Attitudes Toward Violence and Violent Behavior in the School Context: A Systematic Review and Correlational Meta-Analysis

Abstract: Background/Objective Both theoretical proposals and empirical work point to a common concurrence between attitudes toward school violence and violent behavior. Studies often address this issue superficially or within intervention programs. Our objective is to describe the results of a systematic review and to conduct a meta-analysis exploring these associations. Method A systematic review was conducted in the main databases. Effect sizes were calculated and synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
(43 reference statements)
2
2
0
Order By: Relevance
“…This finding can be attributed to the following two reasons. First, this is in accordance with the general findings for attitudes toward violence (López et al, 2022). This has been explained based on gender roles, which follow the idea that boys are more legitimized to use violence to solve conflicts compared to girls (Dill et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…This finding can be attributed to the following two reasons. First, this is in accordance with the general findings for attitudes toward violence (López et al, 2022). This has been explained based on gender roles, which follow the idea that boys are more legitimized to use violence to solve conflicts compared to girls (Dill et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Although some researchers (e.g., Wicker, 1969) in the 1960s advocated for the complete rejection of attitudes as predictors of behaviour, subsequent methodological and theoretical improvements have led to the recognition that attitudes are good predictors of behaviour. For example, the results of several meta-analyses have shown that correlations between attitudes and behaviour can reach moderate correlations in terms of magnitude (e.g., Glasman and Albarracin, 2006;Kim and Hunter, 1993;Pina Lopez et al, 2022). The results obtained in the present study are consistent with the findings of these meta-analyses, with a significant correlation of .59 between attitudes toward cyberbullying and cyberbullying itself.…”
Section: Discussionsupporting
confidence: 91%
“…The current study found a significant positive impact of MVP on mentors’ attitudes related to violence more generally, indicating reduced acceptability and justification for the use of violent strategies to resolve confrontational or challenging circumstances. Previous research has shown that attitudes towards violence and use of violence are positively associated amongst adolescents, and a meta-analysis concluded modifying attitudes is an important aim for school-based violence prevention programmes [ 49 ]. Crucially, in addition to reducing mentors’ attitudes to perpetrating violence themselves, findings demonstrated the programme had a positive impact on mentors’ attitudes related to the efficacy of violence prevention and their willingness to intervene as a witness to violence and abuse perpetrated by others.…”
Section: Discussionmentioning
confidence: 99%